Assessment of knowledge and practice of menstrual hygiene among the female nursing students in a selected private nursing college in Dhaka City - Nahar, Niru Shamsun; Khatun, Ratna; Akter Halim, Khondoker Mahmuda; Islam, Sharmin; Muhammad, Faisal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Adolescent females are often uninformed and inexperienced on most health-related issues including menstruation. The problems of menstrual hygiene are inadequately acknowledged and has not received any proper attention as well. This study was aimed to assess the level of knowledge and practice of menstrual hygiene among the female nursing students in Bangladesh. Methods: A total of 106 female nursing students were selected from Grameen Caledonian College of nursing using purposive sampling technique. A descriptive cross-sectional type of study was used. Data were collected directly using self-administered semi-structured questionnaire developed and was analysed using SPSS version 22.0. Results: In this study more than six-tenths (63.2%) of the respondents were 20 years and below and most of them (74.5%) were unmarried. About 60.4% of them were currently running diploma in nursing and the rest (38.6%) were B.Sc. nursing students. About 72.6% of the respondent’s mothers had above HSC level of education and most of them (61.3%) were from nuclear family. Little above half (51.9%) of the respondents mentioned that menstruation is the uterine bleeding and the majority (67.0%) of the respondents were surprised during their first menstruation. Most of the respondents source of information about menstruation before menarche was sister (95.3%), followed by friend (92.5%), mother (67.9%) and the rest mentioned the teacher (62.3%). About 76.5% of the respondents mentioned that their mode of disposal of absorbents was dustbin and most of them (68.9%) used water and soap to clean their genital area after menstruation. Conclusions: The study was concluded that more than half of the respondents had moderate level of knowledge and practice regarding the menstrual hygiene. Most of the (67.0%) of the respondents were surprised during their first menstruation and close to eight-tenths (79.2%) mentioned they had a regular usual menstrual cycle. There is need for more awareness regarding the information on good menstrual hygiene practices.